FDA regulations and prescription digital therapeutics: Evolving with the technologies they regulate - Watson, Anthony; Chapman, Richard; Shafai, Gigi; Maricich, Yuri A. (Frontiers in Digital Health, 2023)
Technological progress in digital therapeutics—and, in particular prescription digital therapeutics (PDTs)—has outpaced the processes that the Food and Drug Administration (FDA) uses to regulate such products. Digital therapeutics have entered the health care ecosystem so rapidly that substantial misunderstandings exist about how they are evaluated and regulated by the FDA. This review briefly explains the relevant regulatory history of software as medical devices (SaMDs) and reviews the current regulatory landscape in which prescription and non-prescription digital therapeutics are developed and approved for use. These are important issues because PDTs, and digital therapeutics in general, are an explosively growing field in medicine and offer many advantages over conventional face-to-face treatments for the behavioral dimensions of a wide range of conditions and disease states. By allowing access to evidence-based therapies remotely and privately, digital therapeutics can reduce existing disparities in care and improve health equity. But clinicians, payers, and other healthcare stakeholders must appreciate the rigor of the regulatory frameworks within which PDTs are approved for use.